Best Practices in Project Management - Liviu ILIEŞ; Emil CRIŞAN; Ioana Natalia MUREŞAN (Revista de Management Comparat International)
Project management has evolved over time, becoming the principal mean of dealing with change in modern organizations. Best practices have occurred as a result of business evolution and of practicing project management at a global level. Best practices in project management, if followed, increase the chances of success in achieving goals when dealing with projects. In this article we present the concept of best practice, the advantages of using best practices in project management, which are the best practices used today and also a comparison between two of the mostly used best practices methodologies in project management, Project Management Body of Knowledge and Project Cycle Management Guidelines.